Post‐democracy, democratic renewal and the recent history of British politics. Issue 3 (December 2015) - Stears, Marc
Abstract : Informed partly by his experiences inside the Miliband HQ prior to the 2015 general election, Marc Stears asks why Labour's impulse to democratic reform seems to have petered out, and whether the problems of post‐democratic disengagement in fact lie beyond issues of professionalisation, party structures and modern political stylings.